IMPLEMENTASI PROGRAM SMK PUSAT KEUNGGULAN DILIHAT DARI KONSEP 8+i LINK AND MATCH - Wina Ahmanda; Arris Maulana; R Eka Murtinugraha; Shilmi Arifah (Universitas Pendidikan Indonesia (UPI), 2022)
This research is based of the problem or mismatch between vocational education and work, this is also possible to increase unemployment. Therefore, the Directorate of Vocational Education of the Ministry of Education and Culture of the Program of a Vocational School of Vocational High School Excellence which is a qualified for the absorption of Vocational High School graduates. The method used in this study is the descriptive qualitative research method using the case study approach to the case of the implementation program of the Vocational School Excellence in Vocational High School Number 1 in Kemang of modeling design and building information through the concept of 8+i link and match. The results of this study will provide a comprehensive related to the process of implementing the SMK Center of Excellence program through 8+i link and match, so that the application of this program is expected to be able to improve the quality of education so that it is in accordance with the needs of work.